The Phonology of Marvdashti Dialect. Issue 3 (3rd May 2016) - Emadi, Nezam
Abstract : Phonology is one of several aspects of a natural language and it is the study of sound systems of languages. The purpose of this article is to study and describe the phonemic system of the dialect of Marvdashti. Marvdashti dialect belongs to the southwestern branch of New Iranian languages. The article deals with an inventory of Marvdashti dialect sounds and their features and it covers the phonological rules which specify how sounds interact with each other. This study first introduces and examines the consonants and vowels of Marvdashti dialect, and then explores phoneme arrangement, syllable structure and phonological processes such as assimilation, dissimilation, alteration, epenthesis, deletion and methathesis.